Interorganizational Alignment of Strategic Orientations in Supply Chains - Abbade, Eduardo Botti (Revista de Negócios, 2016)
This study argues that Market Orientation, Learning Orientation, Innovation Orientation and Relationship Orientation provide synergic effects to organizations in organizational and interorganizational levels. Two theoretical frameworks are presented in this theoretical essay. The first one considers the organizational level. The second one is regarded to interorganizational relations. This study argues that actors might improve their results and increase joint performance through a strategic alignment along a supply chain. Besides, network features like positioning, structural holes and density might impact on joint performance achieved through this strategic alignment. Thus, this study suggests that Learning Orientation in a competitive environment might harm joint performance, considering that some actors might act opportunistically defending their knowledge acquisition. Future studies should be focused on issues like open innovation, opportunistic behavior and network structures.